War and revolution in Yugoslavia, 1941-1945 : occupation and collaboration - Tomasevich, Jozo 1908- (Stanford Univ. Press, 2001)
Yugoslavia between the wars -- The partition of Yugoslavia -- German and Italy divide Slovenia -- Foreign annexation of Yugoslavia -- The puppet government of Serbia -- The independent state of Croatia: an Italian-German quasi protectorate -- The independent state of Croatia: under German dominance -- The independent state of Croatia: internal problems and policies -- The independent state of Croatia: the rule of lawlessness and terror -- The armed forces of the independent state of Croatia -- The independent state of Croatia: the Bosnian Muslims -- The churches during the occupation and revolution -- The destruction of the Jewish community in Yugoslavia -- Axis exploitation of the Yugoslav economy: part I -- Axis exploitation of the Yugoslav economy: part II -- Further economic consequences of war and exploitation -- Alleged and true population losses -- The end of the collaborationist regimes in Yugoslavia